Poloidally asymmetric potential formation on plasma boundary in axisymmetric magnetic field - Le, Trang; Suzuki, Yasuhiro; Ohtani, Hiroaki; Hasegawa, Hiroki; Moritaka, Toseo (Frontiers in Physics, 2024)
To study the symmetry of electrical potential, we model plasma transport in the edge region of a toroidal device with two spatial dimensions (2D) and three coordinates for velocities (3V) using a Particle-In-Cell (PIC) code. A two-dimensional magnetic field is applied, including poloidal and toroidal components, which are periodic in the poloidal direction. We discover relationships between the magnetic gradient drift and potential formation using PIC simulation, which has not been captured in other numerical models. We find that the inverse aspect ratio influences the asymmetry of the potential in an axisymmetric magnetic configuration.